Dopamine receptor type 2 (DRD2) and somatostatin receptor type 2 (SSTR2) agonists are effective in inhibiting proliferation of progenitor/stem‐like cells isolated from nonfunctioning pituitary tumors. Issue 8 (8th February 2017) - Peverelli, E.; Giardino, E; Treppiedi, D.; Meregalli, M.; Belicchi, M.; Vaira, V.; Corbetta, S.; Verdelli, C.; Verrua, E.; Serban, A. L.; Locatelli, M.; Carrabba, G.; et al.
Abstract : The role of progenitor/stem cells in pituitary tumorigenesis, resistance to pharmacological treatments and tumor recurrence is still unclear. This study investigated the presence of progenitor/stem cells in non‐functioning pituitary tumors (NFPTs) and tested the efficacy of dopamine receptor type 2 (DRD2) and somatostatin receptor type 2 (SSTR2) agonists to inhibit in vitro proliferation. They found that 70% of 46 NFPTs formed spheres co‐expressing stem cell markers, transcription factors (DAX1, SF1, ERG1) and gonadotropins. Analysis of tumor behavior showed that spheres formation was associated with tumor invasiveness (OR = 3, 96; IC: 1.05–14.88, p  = 0.036). The in vitro reduction of cell proliferation by DRD2 and SSTR2 agonists (31 ± 17% and 35 ± 13% inhibition, respectively, p  < 0.01 vs. basal) occurring in about a half of NFPTs cells was conserved in the corresponding spheres. Accordingly, these drugs increased cyclin‐dependent kinase inhibitor p27 and decreased cyclin D3 expression in spheres. In conclusion, they provided further evidence for the existence of cells with a progenitor/stem cells‐like phenotype in the majority of NFPTs, particularly in those with invasive behavior, and demonstrated that the antiproliferative effects of dopaminergic and somatostatinergic drugs were maintained in progenitor/stem‐like cells. Abstract : What's new? One third of pituitary tumors are non‐functioning (NFPTs) producing, but not secreting, gonadotropins, or gonadotropin hormone subunits. Here the authors isolated from the majority of NFPTs, particularly those with invasive behavior, progenitor/stem‐like cells co‐expressing stem cell markers, embryonic pituitary transcription factors and gonadotropins. These cells reproduced anti‐proliferative responses to dopamine and somatostatin analogues observed with bulk tumor cells, underscoring their relevance in the adjuvant medical therapy of NFPTs.